Understanding the Behavior of Sanctuary-Housed Chimpanzees During Public Programs. (3rd July 2020) - Hansen, Bethany K.; Hopper, Lydia M.; Fultz, Amy L.; Ross, Stephen R.
ABSTRACT: At zoos, and some sanctuaries, members of the public can observe the resident animals. Examining the characteristics and consequences of this type of human–animal encounter is important to understand public education and engagement as well as animal behavior and welfare. Zoos typically have a large and consistent visitor presence, and researchers report mixed findings regarding the effects of the visiting public on the behavior of resident primates. In contrast, public visitation at sanctuaries more often occurs sporadically and on a relatively small scale, as compared with zoos, and typically via organized tours or educational events. Owing to these differences, it is necessary to explore the effects of public programs on animals in sanctuary settings in addition to the more comprehensive efforts studying such influences in zoos. Therefore, we observed four groups of sanctuary chimpanzees ( Pan troglodytes ) at Chimp Haven (USA) over one year, including opportunistic observations during public programs. These scheduled, but infrequent, educational events offered visitors the possibility to view chimpanzees in outdoor enclosures and sometimes included staff-led small tours and food and enrichment provision to the chimpanzees. Our aim was to determine whether the 50 chimpanzees' behavior differed when public programs were offered at the sanctuary compared with "baseline" periods. It was found that during these programs chimpanzees spent more time in outdoor enclosures (GLMM: est. = 1.559, SE = 0.309, Z = 5.04, p < 0.001) and increased time feeding (GLMM: est. = 0.754, SE = 0.356, Z = 2.11, p = 0.034) and locomoting (GLMM: est. = 0.887, SE = 0.197, Z = 4.50, p < 0.001) compared with times when public programs were not ongoing. We rarely observed agonistic and abnormal behaviors, potential metrics of welfare, regardless of whether public programs were ongoing. Abnormal behaviors occurred too infrequently for statistical analysis. While the chimpanzees showed some differences in their behavioral repertoire during the public programs, such changes do not suggest that their welfare was compromised as a result of these activities.